The influence of renewable and non-renewable energy on carbon emissions in Pakistan: evidence from stochastic impacts by regression on population, affluence, and technology model - Amin, Azka; bte Mohamed Yusoff, Nora Yusma; Yousaf, Hazrat; Peng, Sun; Işık, Cem; Akbar, Muhammad; Abbas, Shujaat (Frontiers in Environmental Science, 2023)
Concerns about the rising trend of carbon emissions and the resulting negative effects of climate change on human activities have emerged as major issues in recent years. Like other developing countries, Pakistan has one of the most serious challenges of how to mitigate carbon emissions while achieving sustainable development. Using the PLSM 2018-2019 survey, this study attempts to examine the household sector’s green and non-renewable energy usage magnitude, and the share of green and non-renewable energy in Pakistan. Furthermore, this study examines the impact of income, household size, biomass, non-renewable, and clean energy on carbon emissions using the STIRPAT model. It is obvious from the empirical findings that the coefficient of income is positive, whereas the coefficient of income square is negative and statistically significant, which indicates that carbon emissions in the household sector increase at lower income levels, while decreasing as income increases. The household size shows that the population has a positive impact on carbon emissions. The impact of biomass, non-renewable, and clean energy is particularly appealing, as the household sector consumes more biomass and non-renewable energy, which stimulates carbon emissions to rise. In the rural sector, clean energy has a negative but statistically insignificant impact on carbon emissions, showing a greater reliance on biomass and non-renewable energy consumption. Lastly, it is suggested that reducing the use of non-renewable energy in the household sector while increasing the use of green energy could be a policy option for making the environment clean and sustainable.